I keep making some type of mistake on this problem, can someone please show how to work it out? I think maybe I get the signs mixed up. I am supposed to work it using the quadratic formula. s^2 = 9 + s(1-2s) Thanks!!
Follow Math Help Forum on Facebook and Google+
$\displaystyle s^2 = 9 + s(1-2s)$ $\displaystyle s^2 = 9 + s-2s^2$ $\displaystyle 3s^2 -s- 9 =0$ $\displaystyle s = \frac{-(-1)\pm\sqrt{(-1)^2-4\times 3 \times -9}}{2\times 3}=\dots $ can you finish it?
I wasn't distributing the s before using the quadratic formula. Thanks so much!!
View Tag Cloud